Successful salvage of an unstable Girdlestone's excision arthroplasty with a megaprosthesis of the hip - Vaishya, Raju (J Clin Orthop Trauma, 2015)
The functional results after a Girdlestone's excision arthroplasty of the hip are unpredictable with high patient dissatisfaction and complication rates. We report such a case of symptomatic patient, which was managed successfully with a megaprosthesis of the hip with constrained acetabular liner. The use of megaprosthesis for a failed and symptomatic Girdlestone's excision arthroplasty of the hip has not been reported before.